Acquisition and colonization dynamics of antimicrobial-resistant bacteria during international travel: a prospective cohort study. (October 2019) - Schaumburg, F.; Sertic, S.M.; Correa-Martinez, C.; Mellmann, A.; Köck, R.; Becker, K.
Abstract: Objectives: Travellers may be colonized with antimicrobial-resistant bacteria on return, but little is known about colonization during travel. Our objectives were to assess the acquisition and colonization dynamics during the stay abroad for a broad range of antimicrobial-resistant bacteria and resistance phenotypes and to identify risk factors for faecal carriage of antimicrobial-resistant bacteria. Methods: German and Dutch participants ( n = 132) of this prospective cohort study (2016–2018) completed a questionnaire on risk factors and provided daily stool samples before, during, and after travel. Samples were screened for extended-spectrum β-lactamase producing Enterobacterales (ESBL-E), carbapenem-resistant (CarbR-GN), and non-intrinsically colistin-resistant Gram-negative rods (ColR-GN), vancomycin-resistant Enterococcus faecium / faecalis (VRE), and Clostridioides difficile . Results: Colonization rates reached a plateau within a week after departure fluctuating around 48.5% (63/130) and 58.4% (45/77, ESBL-E), 10.4% (11/106) and 23.4% (18/77, ColR-GN), or 3.0% (4/132) and 6.8% (8/118, CarbR-GN). Colonization rates after the travel were 46.2% (61/132, ESBL-E), 9.0% (12/132, ColR-GN), and 3.4% (5/132, CarbR-GN). Travellers carried mcr-1- (15/132; 11.4%) or bla NDM -positive (4/132; 3.0%) Enterobacterales. A vegetarian diet was associated with a lower risk for the acquisition of ESBL-E (OR = 0.4, p 0.04) and ColR-GN (OR = 0.1, p 0.01) during travel in a multivariable model. Similarly, travellers visiting friends and relatives had a lower risk for the acquisition of ESBL-E (OR = 0.3, p 0.009) and CarbR-GN (OR = 0.3, p 0.01). VRE and C. difficile were not detected. Conclusion: The number of travellers with a temporary colonization during the journey exceeded the number of travellers still colonized after return.